2017
DOI: 10.4103/0974-7796.210029
|View full text |Cite
|
Sign up to set email alerts
|

Does prostate size predict the urodynamic characteristics and clinical outcomes in benign prostate hyperplasia?

Abstract: Aims:Bladder outlet obstruction (BOO) in large and small prostates is managed in a similar manner despite considerably different pathophysiology, which can result in higher failure rates. We investigate the clinical and urodynamic features and study the outcome of patients with benign prostate hyperplasia (BPH) according to their prostate size.Subjects and Methods:We prospectively analyzed 100 BPH patients undergoing urodynamic study between January 2015 and August 2016 and divided them into two groups accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
3
2
Order By: Relevance
“…In this study, the values of PSAD of Sri Lankan men were fluctuating around 0.11(mean PSAD) in different age groups and it did not show a gradual linear increase with ageing. A study done in healthy Iranian men confirmed that PSAD was agedependent [8,9] and this is not comparable with the results of this study.…”
Section: Figure 1 Variations Of Mean Prostate Volume With Different A...contrasting
confidence: 98%
“…In this study, the values of PSAD of Sri Lankan men were fluctuating around 0.11(mean PSAD) in different age groups and it did not show a gradual linear increase with ageing. A study done in healthy Iranian men confirmed that PSAD was agedependent [8,9] and this is not comparable with the results of this study.…”
Section: Figure 1 Variations Of Mean Prostate Volume With Different A...contrasting
confidence: 98%
“…However, multiple studies have found that the PV in patients with BPH is not a valid predictor of the diagnosis of BOO or surgical efficacy. 32 33 In this study, we observed no significant differences in postoperative indicators between patients with large and small PVs. In general, the larger the PV volume, the more likely BOO will occur.…”
Section: Discussioncontrasting
confidence: 54%
“…In total, 324 patients with BOO and a prostate volume of <30 mL as measured by transrectal ultrasonography were analyzed 3,7. All patients had LUTS, and conservative treatments (doxazosin 4mg/tamsulosin 0.2 mg once daily ± finasteride 5 mg once daily for 12 weeks) had been ineffective 810.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the patients were divided into a TURP group and PKEP group according to the surgical procedure performed, and the difference in each of the above parameters between the two groups was compared. The inclusion criteria of this study should be all included the following:8,1315 ①prostate volume of ≤30 mL as measured by transrectal ultrasonography;3,7 ②Qmax of ≤15 mL or acute urinary retention or preoperative residual urine volume of ≥100 mL or presence of LUTS caused by benign prostatic obstruction;1619 ③IPSS of >19 points; ④Preoperative cystoscopy to examine benign prostatic obstruction (BPO) and bladder trabeculation. ⑤An interest and ability to participate in this study.…”
Section: Methodsmentioning
confidence: 99%